Explaining cohesion linkages in workgroups: the cooperative communication in collectivism and high power distance workgroup context - Hassan Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study develops a multi-level model to advance research on how cultural context in workplace moderates the relationship between cooperative communication and group cohesion in a collectivist workplace setting. We tested the model by using hierarchical linear modeling (HLM) with the data obtained from 375 employees representing 48 workgroups in a Malaysian organization. It is revealed that at the group level of analysis, cooperative communication is more strongly related to group cohesion-based in the collectivist cultural context in the individual level of analysis. On the other hand, the power distance context in the work group at the individual level of analysis did not moderate the relationship between cooperative communication and group cohesion in the group level of analysis. Practical implications are discussed.